(untitled) (Research, Society and Development, 2024)
Methylphenidate is a stimulant of the Central Nervous System (CNS) used worldwide in the treatment of Attention Deficit/Hyperactivity Disorder (ADHD), which acts mainly by blocking the dopamine transporter (DAT), inhibiting the reuptake of dopamine by SRIs, causing improvement in ADHD symptoms. When carrying out treatment with Methylphenidate, potential adverse effects may arise. This study aimed to analyze the main adverse reactions cited in other literature on Methylphenidate, to evaluate its safety. This is an Integrative Literature Review Study, carried out from the selection of articles that covered the proposed objectives, with results that show the authors’ assessments of adverse reactions related to the use of Methylphenidate. Among the effects observed, psychotic effects, speech changes, tics, cardiovascular risks, and growth retardation are associated with the use of Methylphenidate. From this, it is concluded that effects such as vascular risks, growth retardation, mania, changes in speech, and others related to psychotic effects may be present in patients undergoing treatment with Methylphenidate, impacting the quality of life of those who use it.